1962
DOI: 10.1037/h0045764
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence at adulthood: A twenty-five year follow-up.

Abstract: This paper reports findings from 111 Ss tested with the Stanford-Binet (S-B) at preschool and adolescence who were administered the S-B and WAIS at adulthood. Correlations of preschool IQs with adult S-B and full WAIS IQs are .59 and .64; of adolescent IQs with adult IQs, .85 and .80. Mean S-B IQ increase from adolescence to adulthood is 11 points, indicating that mental growth continues beyond 16 years. Males show more IQ gain after adolescence than do females (p < .01). Girls with high IQs increase least. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1

Year Published

1963
1963
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 11 publications
4
30
1
Order By: Relevance
“…A similar development was also observed for the three hearing impaired persons included in this study. No correlations were observed between the men's I.Q.s as children and I.Q.s obtained at adult age, while significant correlations have been reported in follow-up studies of non-retarded persons (Bradway and Thompson, 1962;Hindley, 1965).…”
Section: Resultscontrasting
confidence: 63%
“…A similar development was also observed for the three hearing impaired persons included in this study. No correlations were observed between the men's I.Q.s as children and I.Q.s obtained at adult age, while significant correlations have been reported in follow-up studies of non-retarded persons (Bradway and Thompson, 1962;Hindley, 1965).…”
Section: Resultscontrasting
confidence: 63%
“…Compared with other behavioral traits, however, IQ scores become remarkably stable after about age six. Brodway and Thompson (1962) reported test-retest correlations of intelligence scores of .85 over a 15-year period from adolescence to adulthood, of .65 over a 10-year period from preschool to adolescence, and of .59 over the 25-year period from preschool to adulthood. In the Fels longitudinal study of 89 children, Kagan and Moss (1962) found a correlation of .54 for intelligence over a seven-year period beginning at ages 3 to 6, and a correlation of .78 over a five-year period beginning at ages 6 to 10. gence have their major impact early in life, and that later environmental influences do little to disturb the early-established rank order of individuals.…”
Section: Stability Of Iqmentioning
confidence: 98%
“…Subject sex and specific instrument were not found to have a significant effect on reliability. A summary table provides expected reliability coefficients, standard error, and percent of persons with IQ change in excess of 15 points, tabulated for combinations of each of the two predictors.Reviews of the temporal stability of individually administered intelligence tests have appeared sporadically over the last 50 years or so (Bradway & Thompson, 1962;Brown, 1933;Zimmerman & Woo-Sam, 1972). What is lacking is an integrative review of studies across instruments; at least, if there is one, we failed to find it.…”
mentioning
confidence: 99%